Comparison of 68Ga-FAPI and 18F-FDG PET/CT in Dermatofibrosarcoma Protuberans. (22nd July 2022) - Wu, Junhao; Zhang, Shumao; Rao, Zijuan; Wang, Yingwei; Zhang, Chunyin
Abstract: Dermatofibrosarcoma protuberans is a rare soft tissue sarcoma with a high recurrence rate. Herein, we present 68 Ga-FAPI and 18 F-FDG PET/CT findings of dermatofibrosarcoma protuberans in a 45-year-old man. Dermatofibrosarcoma protuberans only shows limited FDG uptakes on 18 F-FDG PET/CT, but demonstrated intense tracer uptakes on 68 Ga-FAPI PET/CT. In this case, 68 Ga-FAPI was superior to 18 F-FDG PET/CT in detecting dermatofibrosarcoma protuberans.